Breast-feeding promotion in hospitals and prospective breast-feeding rates during the first year of life in two national surveys 1997–1998 and 2017–2019 in Germany. Issue 9 (16th June 2021) - Hockamp, Nele; Burak, Constanze; Sievers, Erika; Rudloff, Silvia; Burmann, Anja; Thinnes, Merlin; Zahn, Johanna; Lücke, Thomas; Kersting, Mathilde
Abstract: Objectives: The present study aimed to assess the current state of breast-feeding promotion in hospitals and the prevalence of breast-feeding during the first year of life in Germany and to compare the results with a study 20 years earlier. Design: In the studies on 'breast-feeding and infant nutrition in Germany' named 'SuSe', a cross-sectional survey in hospitals was combined with a subsequent prospective survey of breast-feeding and infant nutrition during the first year of life (0·5, 2, 4, 6 and 12 months after birth) in mother–infant pairs who were recruited in the hospitals. Written questionnaires and phone calls were used in SuSe I and web-based questionnaires in SuSe II. Breast-feeding promotion and prevalence were evaluated using recommendations from the WHO and the UNICEF. Setting: Two nationwide surveys SuSe I (1997–1998) and SuSe II (2017–2019). Participants: In SuSe I, 177 hospitals and 1717 mother–infant pairs and in SuSe II 109 hospitals and 962 mother–infant pairs were included. Results: In SuSe II, hospitals implemented seven of the WHO 'Ten Steps to Successful Breastfeeding' to a greater extent than the hospitals in SuSe I. More mothers exclusively breastfed for 4 months (57 % v . 33 %) and continued breast-feeding until 6 (78 % v . 48 %) and 12 months (41 % v . 13 %). In both studies, exclusive breast-feeding decreased between 4 and 6 months of age due to the introduction of complementary feeding. Conclusions: In Germany, breast-feeding habits have come closer to the recommendations over the last 20 years.